Corneal Biomechanics: Measurement and Structural Correlations - Chong, Jillian (Exp Eye Res, 2021)
The characterization of corneal biomechanical properties has important implications for the management of ocular disease and prediction of surgical responses. Corneal refractive surgery outcomes, progression or stabilization of ectatic disease, and intraocular pressure determination are just examples of the many key clinical problems that depend highly upon corneal biomechanical characteristics. However, to date there is no gold standard measurement technique. Since the advent of a 1-dimensional (1D) air-puff based technique for measuring the corneal surface response in 2005, advances in clinical imaging technology have yielded increasingly sophisticated approaches to characterizing the biomechanical properties of the cornea. Novel analyses of 1D responses are expanding the clinical utility of commercially-available air-puff-based instruments, and other imaging modalities—including optical coherence elastography (OCE), Brillouin microscopy and phase-decorrelation ocular coherence tomography (PhD-OCT)—offer new opportunities for probing local biomechanical behavior in 3-dimensional space and drawing new inferences about the relationships between corneal structure, mechanical behavior, and corneal refractive function. These advances are likely to drive greater clinical adoption of in vivo biomechanical analysis and to support more personalized medical and surgical decision-making.